Functional and sensory evaluation of cashew nut spread complemented with date palm and ripe banana (Agriculture, Food, and Natural Resources Journal, 2025)
This study investigated the functional properties and sensory characteristics of cashew nut-based spread, supplemented with date palm and ripe banana, aiming to develop a nutritious and palatable spread. Mixture design was employed to formulate seven blend ratios of cashew nut: date: banana; 63.33:18.33:18.33, 70:10:20, 70:20:10, 60:20:20, 66.67:16.67:16.67, 68.33:18.33:13.33, and 68.33:13.33:18.33. Roasted cashew nut paste, date palm paste, and ripe banana slurry were homogenized according to the ratios from the design and pasteurized at 60 °C for 3 minutes. Functional properties, including spreadability and viscosity, were measured, and sensory evaluation was conducted using a 9-point hedonic scale. Spreadability values ranged from 15.57 N/m to 26.16 N/m, with the highest spreadability recorded in the 70:20:10 formulations. Viscosity ranged from 20.15 to 35.70 N·s/m², with significantly higher (p
Keywords: Banana; Cashew; Spreadability; Viscosity